Comparison of Optical Coherence Tomography Angiography Findings between Healthy Children and Children with Type 1 Diabetes Mellitus and Autoimmune Thyroiditis - Hüseyin Anıl Korkmaz; Ali Devebacak; İbrahim Mert Erbaş; Cumali Değirmenci; Nilüfer Uyar; Filiz Afrashi; Behzat Özkan (Galenos Yayincilik, 2023)
INTRODUCTION: The aim of this study was to compare the development of early diabetic retinopathy (DR) findings, a microvascular complication, between patients with isolated type 1 diabetes mellitus (T1DM) (Group 1), concurrent T1DM and autoimmune thyroiditis (AT) (Group 2), and healthy controls (Group 3), who were matched for age, sex, number, and body mass index for comparison. METHODS: This was a prospective observational study that included individuals aged 10-20 years, and patients in Groups 1 and 2 had been followed up for ≥5 years. None of them developed clinical DR during the follow-up period. Optical coherence tomography angiography (OCTA) was used to evaluate the foveal avascular zone (FAZ) and parafoveal vascular density (PVD) for the development of early DR. OCTA findings were compared between patients and healthy controls. RESULTS: Thirty-five individuals were included in each of the groups. The mean FAZ and PVD differed significantly between the three groups (FAZ, p=0.016; PVD, p=0.006). The mean FAZ was higher in Groups 1 and 2 than in Group 3 (p=0.013 and p=0.119, respectively). The mean PVD was lower in Groups 1 and 2 than in Group 3 (p=0.007, respectively). No significant difference was found between Groups 1 and 2 in terms of the mean FAZ and PVD (p=0.832 and p=0.653, respectively). The mean glycated hemoglobin (HbA1c) level was significantly correlated with FAZ and PVD (FAZ: r=0.496, p<0.001; PVD: r=-0.36, p=0.001). DISCUSSION AND CONCLUSION: In patients with T1DM who did not develop clinical DR, OCTA findings revealed an increase in FAZ, which was associated with higher HbA1c levels. The mean PVD was significantly lower in the group with coexisting AT and T1DM than in the control group. These results suggest that the coexistence of AT and T1DM can contribute to the development of microvascular complications. However, studies with larger patient series are required.